ANALYSIS OF COCONUT SHELL CHARCOAL PRODUCTION PLANNING IN LEOK I VILLAGE, BIAU DISTRICT, BUOL REGENCY (Case Study of Arang Tampurung Business): ANALISIS PERENCANAAN PRODUKSI ARANG CANGKANG KELAPA DI DESA LEOK I, KECAMATAN BIAU, KABUPATEN BUOL (Studi Kasus Usaha Arang Tampurung) - Suteno, Faldo; Ramlawaty, Ramlawaty; Aqfir, Aqfir (STIE MUJAHIDIN TOLITOLI, 2024)
The type of research used in this research is descriptive research with a qualitative approach, namely explaining and describing the phenomena that occur. The selection of the type of descriptive research is based on the way the researcher obtains data, namely by field observation, interviews and documentation. Jane Richie in Lexxy J. Meleong (2014: 6) explains that qualitative research is research experienced by research subjects, for example behavior, perceptions, motivation, actions and so on, as a whole, and by means of descriptions in the form of words and language in a natural special contest, from the explanation above, descriptively regarding the differentiation strategy process. This research was carried out in Leok I Village, Biau District, Buol Regency. The determination of this location was based, among other things, on considering the problem of shell charcoal production analysis in Leok I Village. The time this research was carried out was for three months, namely from March to May 2023.The production planning for the shell charcoal business is well structured, starting from the raw materials for the production process to the marketing location. Usually one month of production produces 16 tons, producers or business owners sell their products to the island of Java. The result is 48,000 kg of shells or the same as 16 tons of charcoal produced in 4 weeks or 1 month which is sold to the island of Java. 1 kg is sold for IDR 10,000 ,- x 16,000 Kg = IDR 160,000,000.-